2014
DOI: 10.1159/000351680
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Disparities of Children among Southeast Asian Immigrant Women in Arranged Transnational Marriages in Taiwan

Abstract: This study assessed the oral health disparities and oral health care needs of children whose parents are Southeast Asian immigrant women in arranged transnational marriages. We used the baseline data of the Lay Health Advisor Approach to Promote Oral Health Program (LHA-POHP) to explore the disparities in oral health between immigrant and native children, and the factors associated with their oral health. A cross-sectional community-based study was conducted to collect data from mothers and their preschool chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 18 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Currently, the prevalence of interdental caries in young Taiwanese children is high. However, less than half of parents in Taiwan use dental floss to clean their children’s interdental surfaces [8,9,16]. Similarly, in this study, regardless of the group, just 22% of immigrant parents and 41% of native parents used dental floss to clean their children’s interdental surfaces.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Currently, the prevalence of interdental caries in young Taiwanese children is high. However, less than half of parents in Taiwan use dental floss to clean their children’s interdental surfaces [8,9,16]. Similarly, in this study, regardless of the group, just 22% of immigrant parents and 41% of native parents used dental floss to clean their children’s interdental surfaces.…”
Section: Discussionmentioning
confidence: 57%
“…A significantly higher number of children with immigrant parents had untreated caries teeth, compared with native children, and almost one out of three had SECC. Nevertheless, the average number of filled teeth was low in immigrants, which demonstrated that the immigrant children had worse oral health and higher dental treatment requirements [9]. Children from minority families have worse oral health outcomes and use oral healthcare services less frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Taiwan, there have been several previous studies regarding medical care for immigrant workers and new residents (immigrants by marriage) since the introduction of policy for receiving immigrant workers in 1992. However, most of the local studies have focused on the health of immigrant women and their children, such as peripartum/postpartum care, oral health, and transcultural adaptation and psychological illness [10,11,12,13]. Studies into immigrant fishermen’s health and their medical care remain scarce and are universally ignored by the media.…”
Section: Discussionmentioning
confidence: 99%
“…However, no such approach had been applied in the oral health-care field. The 5-year Lay Health Advisor Approach to Promote Oral Health Program (LHA-POHP) was first implemented in Kaohsiung area in 2011, Taiwan Lin et al, 2014]. It was designed to reduce or eliminate caries disparities in access to dental care in preschool children of Southeast Asian immigrant women.…”
Section: Introductionmentioning
confidence: 99%